2013
DOI: 10.1371/journal.pone.0079969
|View full text |Cite
|
Sign up to set email alerts
|

Building a DNA Barcode Reference Library for the True Butterflies (Lepidoptera) of Peninsula Malaysia: What about the Subspecies?

Abstract: The objective of this study was to build a DNA barcode reference library for the true butterflies of Peninsula Malaysia and assess the value of attaching subspecies names to DNA barcode records. A new DNA barcode library was constructed with butterflies from the Museum of Zoology, University of Malaya collection. The library was analysed in conjunction with publicly available DNA barcodes from other Asia-Pacific localities to test the ability of the DNA barcodes to discriminate species and subspecies. Analyses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 42 publications
0
35
0
Order By: Relevance
“…In a few cases, species pairs sharing DNA barcodes are either very closely related or known to hybridize regularly; consequently, it is not possible to identify them exclusively through DNA barcoding (Dincȃ et al 2011). However, cases of introgressive hybridization have seldom been reported for butterflies (Wilson et al 2013). Furthermore, Smith et al (2012) reported no obvious association between DNA barcode sharing and Wolbachia infection after screening 539 174 DNA barcodes from Lepidoptera (a finding consistent with Linares et al 2009).…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…In a few cases, species pairs sharing DNA barcodes are either very closely related or known to hybridize regularly; consequently, it is not possible to identify them exclusively through DNA barcoding (Dincȃ et al 2011). However, cases of introgressive hybridization have seldom been reported for butterflies (Wilson et al 2013). Furthermore, Smith et al (2012) reported no obvious association between DNA barcode sharing and Wolbachia infection after screening 539 174 DNA barcodes from Lepidoptera (a finding consistent with Linares et al 2009).…”
Section: Discussionmentioning
confidence: 81%
“…This included species from the families Hesperiidae and Lycaenidae that are difficult to identify using wing morphology (Koh and Sodhi 2004). Although the number of butterfly species in China (1223; Chao 2000) is similar to Peninsular Malaysia (1100; Wilson et al 2013), the number of available DNA barcodes for butterflies from China in BOLD (331) is three times lower than from Peninsular Malaysia (1247). Consequently, most of the DNA barcodes generated for this study were identified based on matches to DNA barcodes from Peninsular Malaysia for which a DNA barcode reference library is available (Wilson et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This lack of molecular support was also observed among butterflies by Braby, Eastwood & Murray (2012), who called for an integrative concept of subspecies combining phylogenetic support, phenotype distinction and allopatric distribution. In contrast, DNA barcoding of Malaysian butterflies found phylogenetic support for 84% of subspecies (Wilson, Sing & Sofian-Azirun, 2013). The deepest theoretical reflection on infraspecific delimitation in plant taxonomy to date remains the review carried out by Hamilton & Reichard (1992).…”
Section: Introductionmentioning
confidence: 99%